Islamic Argument for Multiculturalism - Syahriyah, Ummi Ulfatus; Maidah, Chusnul (Proceeding International Conference on Religion, Science and Education, 2025)
This research aims to provide Islamic arguments against the ideology of multiculturalism. In the context of Indonesia, we cannot be separated from pluralism because Indonesia is a multicultural nation. The variety of religions and cultures is a wealth that must be knitted together. However, an incomplete view on multiculturalism will only obscure its meaning. This research uses a library research method with documentation techniques, reading various literature to be analyzed. The results show that Islam has a spirit that is in line with multiculturalism, but in recognizing and respecting differences, Islam provides limits in the social sphere, not to touch the realm of belief and worship.